TERORISME DI ERA KONVERGENSI - A Zahid (Jurnal Sosiologi Reflektif, 2018)
This article discusses about the relationship between media and terorism in convergence era. The object was terorism news in TV One. Broadcasting of terorism through media in convergence era demanded to hold tightly of ethical principles of journalism. If not, the media would be a tool spreading terror out to society. This study was a qualitative research using descriptive method because this research aimed to get answer related to perception and opinion thereby requiring detailed quali. Data analysis was carried out using Miles and Huberman’s approach, consisting of data reduction, data display, and conclusion drawing. Data validation was conducted using source triangulation to recheck the obtained data.